2018
DOI: 10.1111/cas.13542
|View full text |Cite
|
Sign up to set email alerts
|

Significance of tumor‐infiltrating lymphocytes before and after neoadjuvant therapy for rectal cancer

Abstract: Neoadjuvant therapy for locally advanced rectal cancer is becoming increasingly common. However, biomarkers predicting the response to neoadjuvant therapy have not been established. Tumor‐infiltrating lymphocytes (TILs) have a crucial effect on tumor progression and survival outcome as the primary host immune response, and an antitumor immune effect has been reported to contribute to the response to radiotherapy and chemotherapy. We investigated the significance of TILs before and after neoadjuvant treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
79
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 41 publications
11
79
0
1
Order By: Relevance
“…Despite the above limitations, higher post-TACE sTIM-3 levels in complete responders may be attributed to the greater extent of tumor infiltration by TIM-3+ T lymphocytes in patients with better response to treatment. This finding has been previously described in cases of complete response to chemotherapy in other types of cancer [36]. Furthermore, a recent study in HCC patients has shown that yttrium-90 (Y90)-radioembolization (RE) induces an increase of PD-1+/TIM-3+ CD8+ T cells at 3 months post-treatment.…”
Section: Discussionsupporting
confidence: 72%
“…Despite the above limitations, higher post-TACE sTIM-3 levels in complete responders may be attributed to the greater extent of tumor infiltration by TIM-3+ T lymphocytes in patients with better response to treatment. This finding has been previously described in cases of complete response to chemotherapy in other types of cancer [36]. Furthermore, a recent study in HCC patients has shown that yttrium-90 (Y90)-radioembolization (RE) induces an increase of PD-1+/TIM-3+ CD8+ T cells at 3 months post-treatment.…”
Section: Discussionsupporting
confidence: 72%
“…Neoantigen specific T cell priming is important for the efficacy of CRT, and immune checkpoint molecules may be therapeutic targets to achieve even better responses in rectal cancer. Mouse models have shown that the efficacy of radiotherapy largely depends on CD8+ T cells; the presence of pretreatment CD8+ TILs correlated with better response to radiotherapy or chemotherapy in breast, lung, head and neck, anal, and rectal cancer. However, most studies using pre‐CRT biopsies in rectal cancer did not analyse TIL and stromal lymphocytes separately.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models have shown that the efficacy of radiotherapy largely depends on CD8+ T cells; the presence of pretreatment CD8+ TILs correlated with better response to radiotherapy or chemotherapy in breast, lung, head and neck, anal, and rectal cancer. However, most studies using pre‐CRT biopsies in rectal cancer did not analyse TIL and stromal lymphocytes separately. One study that did analyse the two populations separately found that pre‐CRT CD8+ TIL density was associated with favourable TRG but not with improved RFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could mean that the pre-treatment composition of the tumor microenvironment is of less importance than the anti-tumor immune response induced by the (chemo)radiotherapy. However, this is not supported by multiple studies that do show an association between the pre-treatment presence of TILs and treatment outcome [14,55,56]. The correlation between biomarkers and OS, DFS, and LRC was assessed in a Cox proportional hazards regression.…”
mentioning
confidence: 96%